INHIBITIVE PROPERTIES OF Garcinia kola (GK) IN ALKALINE MEDIUM OF ALUMINUM ALLOY (AA4007) (Nigerian Journal of Technology, 2024)
The application of  corrosion inhibitors is a more effective strategy tomitigate the impacts of aluminum corrosion. Phytochemical analysis, gravimetric technique, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) were used to investigate the inhibitory potentials of Garcinia kola aqueous leave extract for the corrosion of aluminum alloy (AA4007) in 1 M NAOH. The highest inhibition efficiency obtained was 98.5%.   The result from the analyses collaborated that the leaf extract is a good inhibitor. The Langmuir,  Freundlich and Temkin isotherm is in agreement that the inhibitor is physisorption. Garcinia kola showed high corrosion inhibition efficiency on aluminum alloy.